SARAH BERNHARDT AND THE STYLISTICS OF THE JEWELRY ART NOUVEAU IN FRANCE AT THE TURN OF THE XIX AND XX CENTURIES (Revista Inclusiones, 2020)
The research object is the phenomenon of the influence of the actress Sarah Bernhardt on creating the stylistics of the French version of the jewelry Art Nouveau. The article emphasizes the poor bibliography as regarding the jewelry art of this period, as well as the creative work of specific artists. There is given a review analysis of the main properties of modern in jewelry art, stylistic attributes are prioritized, as well as the usage of new materials, techniques, aiming for new forms and composition decisions in the presence of reminiscences of the jewelry art of previous epochs, which is the reason for some eclecticism of a number of works. With the example of the tandem of S. Bernhardt as one of the most requested actresses of the epoch along with A. Mucha, G. Fouquet and R. Lalique as the most famous jewelers and designers of that time the article reviews the role of famous artistic personalities in establishing the career of new jewelry masters.